High density solid fuel ramjet fuel based on 1, 6-hexanediol diglycidyl ether and methyltetrahydrophthalic anhydride. (15th October 2020) - McDonald, Brian; Rice, Jeremy; Hayes, Brian; Marshall, Chris; Pledger, Larry; Myers, Doug; Jones, Dan
Abstract: A solid fuel ramjet fuel (SFRJ) is developed to have high material density and net impulse density. Theoretical performance and thermochemical analyses are performed on a wide range of polymers as potential fuel candidates leading to an emphasis on epoxies. The compositions of these epoxy thermoset polymers are selected based on previous performance analyses identifying polyethers as preferred materials. Accordingly, a selection of epoxy resins and curatives are independently theoretically evaluated for their fuel value in the SFRJ application. A material is made from the combination of the highest performing materials which are 1, 6-hexanediol diglycidyl ether and methyltetrahydrophthalic anhydride as the epoxy constituent and curative respectively. The material is further characterized by conducting thermogravimetric and differential scanning calorimeter analyses, bomb calorimetry, pyrolyzer gas chromatography mass spectroscopy, and direct connect fuel grain testing. An examination of the collected data suggests that this material represents an excellent candidate for SFRJ applications. The test data shows that the material has a relatively low temperature for the onset of decomposition and decomposes into a predominance of gaseous species that have autoignition temperatures lower than the peak decomposition temperature. The fuel grain testing demonstrates stable combustion and acceptable regression rates.